DEVELOPMENT OF CARTOON STRIPS AS A SOURCE FOR LEARNING ENGLISH - Putri Hardini, Siti Sugesti; Jaya, Aswadi; Hermansyah (Universitas PGRI Palembang, 2025)
The purpose of this research is to develop cartoon strips as a source of English learning for class VIII students. The research method used Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). To ensure the feasibility of the cartoon strips media being developed, aspects of validity, practicality and effectiveness were evaluated. The subjects in this research were class VIII, totaling 36 students. Data was collected through questionnaires and field trials. The research results showed that the cartoon strip learning that was developed was declared valid with a percentage of 81.3% so that the open module that had been prepared could be implemented according to plan. Therefore, this cartoon strip is considered practical with a percentage of 85.5% and an effectiveness level of 89.7% and this cartoon strip is proven to be interesting for students. By learning this cartoon strip, it can motivate and facilitate students to be more active in learning English and become a source of learning English.